Femtosecond laser cleaning of historical paper with sizing - Ersoy, Tansu; Tunay, Tugba; Uguryol, Mehmet; Mavili, Gurcan; Akturk, Selcuk (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2014)
Lasers have served as cleaning tools for historical objects and artworks for about 40 years. In many cases, superior results of laser cleaning were achieved with respect to traditional methods. In this technique, contaminations on the surface of the object are ablated by laser irradiation. In order to apply laser cleaning method to fragile materials such as paper made of cellulose or parchment, heat deposition to the bulk should be minimal, to prevent damage. In this work, it is demonstrated that laser pulses with femtosecond (fs) duration can exhibit non-thermal ablation of contaminants on paper samples. In particular, laser cleaning studies are concentrated on paper samples with sizing. Fs laser cleaning is performed on artificially soiled and aged samples, as well as on historical ones. The laser used in the experiments has pulse duration of 550 fs and 1030 nm center wavelength. The fluence of the laser is varied and the post-cleaning statuses of samples are investigated. The analyses are color changes, fiber integrity, chemical composition changes and mechanical strengths. These results show that fs lasers can be very efficient in cleaning paper samples, yielding minimal discoloration and no damage to fibers distinguishable on microscopic examination. The presence of sizing also provides further protection against possible side effects. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Laser cleaning; Historical paper; Sizing; Femtosecond laser; NANOSECOND; PARCHMENT; ABLATION; CONSERVATION; DIAGNOSTICS; PICOSECOND; Archaeology; Art; Chemistry; Geology; Materials Science; Spectroscopy